Online Campaigns for Combating the Spread of Pandemic of Covid-19: Building Collective Awareness of School Children at Tatah Masjid Village, Batola Regency - ahmad kailani (UMBanjarmasin, 2021)
The Pandemic of Covid 19 has spread rapidly throughout the globe. Various ways have been used to combat this disease. Not only curative ways, but preventive ways are also performed. One of the attempts is that health promotion containing messages for increasing people’s awareness of personal hygiene. School children, as society members who are vulnerable to this virus, need to be informed about the virus and simple ways to prevent from this virus attack. However, during the pandemic, face to face interaction is prohibited since it may transmit the virus among people. Therefore, to maximize the socialization of this disease, online campaigns were undertaken to educate people, in particular, school children in Tatah Masjid Village. The online health promotion was undertaken by distributing online leaflets through social media such as Instagram and informative videos through YouTube. People’s responses toward the program was positive indicated by like, comments, and shares displayed on the social media used. The implimentation of this acivity, for the future hope, is expected to build personal awareness of school children to do preventive attempts of the Covid-19 spread autonomously.